Conceptual framework of applying CoI-based blended learning approach to enhance students’ vocabulary and vocabulary learning motivation - Qiu Chuane (PLoS ONE, 2025)
In China, secondary school students enrolled in vocational stream frequently have difficulties in mastering the English language. The mechanical traditional way of teaching and their lack of vocabulary toward the target language often demotivate them in learning. This quasi-experimental study aims to investigate the use of CoI-based blended learning approach to enhance students’ Vocabulary Test Scores (VTS) and Vocabulary Learning Motivation (VLM) in Chinese secondary vocational English as a Foreign Language (EFL) classrooms. Explanatory sequential mixed methods approach was applied by this study. Using purposive sampling method, a total of 86 first-year students at a Technician College in Chongqing, China was allocated to an experimental group (n = 44) and a control group (n = 42). Instruments involving a researcher-developed vocabulary test and VLM questionnaire were used to gather quantitative data, whilst a semi-structured interview was used to gather qualitative data. Both the quantitative and qualitative findings revealed that CoI-based blended learning approach had the potential of enhancing students’ VTS and VLM. Consequently, this research may provide other EFL practitioners with a CoI-based Blended Learning Conceptual Framework for enhancing students’ VTS, VLM and insights into the potential of blended teaching supplements through the lens of the CoI framework.